Pro Oracle Application Express 4 - Fox, Tim; Scott,John Edward; Spendolini,Scott; SpringerLink (Online service). (Berkeley, CA Apress Imprint: Apress, 2011)
Pro Oracle Application Express 4 is your key to mastering one of the most innovative products to come out of Oracle in years. Application Express, termed "APEX" for short, is fast becoming one of the easiest and most widely-used of tools for creating enterprise-level applications that run against an Oracle database. APEX is easy enough for power users to create ad-hoc applications atop something more reliable than a spreadsheet. Yet APEX is powerful and extensible enough to enable fully-scalable, enterprise-level applications that are accessed by thousands of users. Authors Tim Fox, John Scott, and Scott Spendolini take you to the professional level in developing for Application Express. They show how to handle user authentication in enterprise environments and how to extend APEX by writing components based upon Oracle's new plug-in architecture. You'll learn to deal with localization issues such as time zones and translations, and to customize the look and feel of an APEX website to blend in with your corporate branding strategy. The authors also cover web service development, performance and scalability, and the production issues that you encounter in enterprise-level deployments. Many years of experience in solving the "hard problems" are coalesced in this book to help you, the reader, take advantage of all that APEX has to offer. Focuses on high-end, enterprise-level development Covers new features such as plug-ins and Websheets Introduces the new interface released with APEX 4.0
Introduction -- Development best practices -- Authentication and user management -- Conditions and authorization schemes -- Data security -- Navigation and layout -- Reports and charts -- Dynamic actions -- Websheets -- Reporting and printing -- Themes and templates -- Localization issues -- Plug-ins -- Web services -- Performance and scalability -- Production issues -- APEX dictionary.
Electronic reproduction.
Keywords: Oracle (Computer file); Relational databases; Application software; Electronic books